2018
DOI: 10.1111/dom.13282
|View full text |Cite
|
Sign up to set email alerts
|

Fimasartan increases glucose‐stimulated insulin secretion in patients with type 2 diabetes and hypertension compared with amlodipine

Abstract: Compared with amlodipine, fimasartan increased late-phase glucose-stimulated insulin secretion in patients with type 2 diabetes and hypertension. This finding suggests that ARBs would be more beneficial in such patients compared with other classes of anti-hypertensives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Although a recent clinical study reported an effect of increased insulin secretion for fimasartan in type 2 diabetic patients, 23 relatively few studies have described the effects or mechanism of fimasartan-mediated improvements in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent clinical study reported an effect of increased insulin secretion for fimasartan in type 2 diabetic patients, 23 relatively few studies have described the effects or mechanism of fimasartan-mediated improvements in glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…An open‐label, active comparator‐controlled, crossover study also demonstrated that when compared with other antihypertensive agents, ARBs treatment are more beneficial in subjects with T2DM through increasing late‐phase glucose‐stimulated insulin secretion . 30 To the best of our knowledge, few studies examined the relationship between ARBs treatment and insulin secretion in patients with T2DM, though some studies were conducted in patients with prediabetes 31 . Preserving β ‐cell function is vital to patients with T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…14 According to the report by Yang et al, insulin secretion is increased by fimasartan treatment in patients with type 2 diabetes and hypertension, compared with amlodipine. 15 These findings suggest that fimasartan combined with linagliptin would be more beneficial in such patients. However, to our knowledge, there are no reports of studies on the interaction between fimasartan and linagliptin.…”
Section: Introductionmentioning
confidence: 95%